2019
DOI: 10.1093/cid/ciz978
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Use Does Not Preclude Diagnosis or Reduce Disease Severity in Clostridiodes difficile Infection

Abstract: Background To optimize utility of laboratory testing for Clostridiodes difficile infection (CDI), the 2017 Infectious Diseases Society of America–Society for Healthcare Epidemiology of America (IDSA-SHEA) clinical practice guidelines recommend excluding patients from stool testing for C. difficile if they have received laxatives within the preceding 48 hours. Sparse data support this recommendation. Methods Patients with new-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The rationale behind the recommendation is that patients taking laxatives may be asymptomatically colonized with C. difficile , resulting in unnecessary antibiotic treatment ( 56 58 ). Furthermore, some studies identified laxatives as a risk factor for developing CDIs or recurrent CDIs ( 59 61 ), and a recent study found that the proportions of severe CDIs were similar between patients taking and those not taking laxatives ( 62 ). However, there have also been some studies that suggest that laxatives are not a risk factor for developing CDIs ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind the recommendation is that patients taking laxatives may be asymptomatically colonized with C. difficile , resulting in unnecessary antibiotic treatment ( 56 58 ). Furthermore, some studies identified laxatives as a risk factor for developing CDIs or recurrent CDIs ( 59 61 ), and a recent study found that the proportions of severe CDIs were similar between patients taking and those not taking laxatives ( 62 ). However, there have also been some studies that suggest that laxatives are not a risk factor for developing CDIs ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind the recommendation is that patients taking laxatives may be asymptomatically colonized with C. difficile, resulting in unnecessary antibiotic treatment (55)(56)(57). Furthermore, some studies identified laxatives as a risk factor for developing CDIs or recurrent CDIs (58-60) and a recent study found the proportion of severe CDIs was similar between patients taking and not taking laxatives (61). However, there have also been some studies that suggest laxatives are not a risk factor for developing CDIs (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration when implementing diagnostic stewardship interventions is assessing the potential for unintended adverse consequences by more restrictive testing approaches. A recent study found similar rates of serious outcomes among patients who tested positive for C difficile who did and did not receive laxatives and raises concern that exclusion of patients receiving recent laxatives from testing could lead to delayed or missed diagnoses of severe CDI [ 23 ]. As many institutions have incorporated CCDS tools that restrict testing in the setting of laxatives, the findings of the above study may have important implications.…”
Section: Discussionmentioning
confidence: 99%